2012
DOI: 10.1111/j.1469-0691.2011.03569.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological diagnosis of Japanese spotted fever using formalin-fixed, paraffin-embedded skin biopsy specimens Usefulness of immunohistochemistry and real-time PCR analysis

Abstract: Japanese spotted fever (JSF) is caused by Rickettsia japonica, and lethal cases are reported yearly in southwest Japan. We thus established the method of diagnosing JSF by immunohistochemistry (IHC) and real-time PCR (RT-PCR) using formalin-fixed, paraffin-embedded skin biopsy specimens. Two monoclonal antibodies were used for IHC, and the 17k genus common antigen gene served as the target of RT-PCR. We collected skin biopsy (n = 61) and autopsy (n = 1) specimens from 50 patients clinically suspected of JSF. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Sequencing of the PCR‐amplified fragments is useful for confirming the bacterial species. In our previous study, genomic DNA fragments of Rickettsia japonica were demonstrated in FFPE sections of skin biopsy of Japanese spotted fever by real‐time PCR and sequencing …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing of the PCR‐amplified fragments is useful for confirming the bacterial species. In our previous study, genomic DNA fragments of Rickettsia japonica were demonstrated in FFPE sections of skin biopsy of Japanese spotted fever by real‐time PCR and sequencing …”
mentioning
confidence: 99%
“…In our previous study, genomic DNA fragments of Rickettsia japonica were demonstrated in FFPE sections of skin biopsy of Japanese spotted fever by real-time PCR and sequencing. 17 We tried herein to detect Ck in FFPE biopsy specimens of GM both by low-specificity immunostaining and by realtime PCR.…”
mentioning
confidence: 99%
“…Antigens of Rickettsia japonica (a causative agent of JSF) were undetectable by two mouse monoclonal antibodies (clones X1 and S3). 5 A mouse monoclonal antibody to B. henselae (clone: H2A10, Biocare Medical, Concord, CA, USA) diluted at 1:100 identified strongly positive signals in the cytoplasm of macrophages and endothelial cells at the site of ulceration (Fig. 2d).…”
Section: Bartonella Henselae Infection Caused By Cat Flea Bitementioning
confidence: 99%
“…Histologically, the eschar was associated with marked lymphoplasmacytic reactions in the deep dermis through subcutaneous tissue, unusual findings in JSF. 5 We have evaluated 50 cases of JSF with skin biopsy specimens for immunohistochemical and PCR demonstration of R. japonica, and both significantly contributed to an early diagnosis of JSF. 5 In our case, the same strategy was effective for making a definite/differential diagnosis of B. henselae infection.…”
Section: Bartonella Henselae Infection Caused By Cat Flea Bitementioning
confidence: 99%
See 1 more Smart Citation